ANALISIS KOMPONEN KIMIA BEBERAPA KUALITAS GAHARU DENGAN KROMATOGRAFI GAS SPEKTROMETRI MASSA - Gunawan Pasaribu; Totok K. Waluyo; Gustan Pari (BRIN Publishing, 2013)
This paper presents the resin content and the chemical composition of some of agarwood quality using gaschromatography mass spectrometry. The quality of agarwood that tested are kemedangan C, teri C, kacangan C and superAB. The results showed that the extracts yield of various solvent of agarwood are decreasing from super AB towardkacangan C, teri C, and kemedangan C. The agarwood samples contain furan compounds and ester aromatic groups thatresponsible for agarwood's nice scent. This research showed that traditional agarwood quality classification were notobjectives.